On Numerical Arguments in Policymaking - Andone, Corina (Informal Logic, 2022)
The use of numerical arguments has become part and parcel of evidence-based policymaking, serving increasingly as scientific evidence which is used to back up policy decisions and to convince citizens of the acceptability of those decisions. But numerical arguments and their quality and potential persuasive role in the specific institutional context of policymaking have received little treatment within argumentation theory. This paper endeavours to explain the forms, functions, and quality of numerical arguments in policymaking.